Mat Pilates and belly dance: Effects on patient-reported outcomes among breast cancer survivors receiving hormone therapy and adherence to exercise - Boing L.* (2023)
© 2022 Elsevier LtdBackground: Breast cancer treatment leads to several side effects. Exercise can help to reduce these side effects. However, it is unknown whether a mat Pilates or a belly dance intervention can improve the patient-reported outcomes of these women. Objective: Examine the effects of a 16-week exercise intervention (mat Pilates or belly dance) on patient reported outcomes (PROs) among breast cancer survivors, at 16 weeks, six months, and 12 months; and investigate sociodemographic and clinical predictors of intervention adherence. Methods: Seventy-four breast cancer survivors who were receiving hormone therapy were randomly allocated into mat Pilates (n = 25), belly dance (n = 25) or control group (educational sessions) (n = 24). Mat Pilates and belly dance groups received a 16-week intervention, delivered three days a week and 60 min a session. The control group received three education sessions and continue usual care. The patient reported outcomes assessed were depressive symptoms (Beck Depression Inventory), stress (Perceived Stress Scale), optimism (Life Orientation Test), fatigue (FACT-F), sleep quality (Pittsburgh Sleep Quality Index) and pain (VAS), clinical and sociodemographic characteristics, and habitual physical activity (IPAQ short). Results: All three groups showed a significant improvement in fatigue, and this effect was maintained during follow-up. No significant effects were found for depressive symptoms, optimism, stress, or pain. A history of exercise prior to breast cancer and be inactive after diagnosis were significant predictors of adherence to interventions. Conclusion: Mat Pilates, belly dance and a few educational sessions can be effective in improving fatigue after 16 weeks of intervention. Registration: ClinicalTrials.gov (NCT03194997).